Discourses of war and peace - Hodges, Adam (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; War, discourse, and peace -- Justifying War: 'New World Coming': Narratives of the Future in U.S. Post-Cold War National Security Discourse -- The Generic U.S. Presidential War Narrative: Justifying Military Force and Imagining the Nation -- The Discursive Battlefield of the "War on Terror": Enabling Strategies for Garnering Public Support in the Rhetoric of George W. Bush and Osama bin Laden -- World of the Impolitic: A Critical Study of the British WMD Dossier -- Negotiating Military Deployment: Culture Clash: Framing Peacekeeping and its Role in a Canadian Context -- Promising without speaking: military realignment and political promising in japan -- Responding to Armed Conflict: "Everyone Has Their Particular Part to Play": Commensuration in the Northern Irish and Palestinian Victims' Rights Movements -- Reasonable Affects: Moroccan Family Responses to Mediated Violence -- Promoting Peace: Performing Peace: The Framing of Silence in a Quaker Vigil -- Narrating War and Peace at Battle Ruins: Okinawan Tourism-Activism Discourses